2018
DOI: 10.3390/microorganisms6010020
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptional Activation of Genes Encoding Soluble Methane Monooxygenase in a Facultative Versus an Obligate Methanotroph

Abstract: Methanotrophs are a specialized group of bacteria that can utilize methane (CH4) as a sole energy source. A key enzyme responsible for methane oxidation is methane monooxygenase (MMO), of either a soluble, cytoplasmic type (sMMO), or a particulate, membrane-bound type (pMMO). Methylocella silvestris BL2 and Methyloferula stellata AR4 are closely related methanotroph species that oxidize methane via sMMO only. However, Methyloferula stellata is an obligate methanotroph, while Methylocella silvestris is a facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The high abundance of Mmo proteins in thiosulfate-grown cells was unexpected since these cells did not consume oxygen in the microrespirometry experiments when provided with methane as the sole substrate ( Table 2 ). Expression of some genes encoding MMO in the absence of methane was observed previously ( 19 , 98 ). The presence of these proteins in all of the conditions tested might be an adaptive regulatory trait for rapid induction of methane oxidation in response to dynamic fluxes of methane in wetland environments.…”
Section: Resultssupporting
confidence: 71%
“…The high abundance of Mmo proteins in thiosulfate-grown cells was unexpected since these cells did not consume oxygen in the microrespirometry experiments when provided with methane as the sole substrate ( Table 2 ). Expression of some genes encoding MMO in the absence of methane was observed previously ( 19 , 98 ). The presence of these proteins in all of the conditions tested might be an adaptive regulatory trait for rapid induction of methane oxidation in response to dynamic fluxes of methane in wetland environments.…”
Section: Resultssupporting
confidence: 71%
“…Methylocella sp. PC1 and PC4 from Pipe Creek exhibited faster growth rates on methane and propane (up to 0.04 h −1 , Table 2) compared to those previously reported for Methylocella (0.01–0.02 h −1 on methane and 0.005–0.015 h −1 on propane) [49, 102, 103]. As with Methylocella silvestris BL2 [49], they grew under methane and propane simultaneously and could also utilise non-gaseous multicarbon compounds, including acetate, pyruvate and succinate (Additional file 1: Table S1).…”
Section: Resultsmentioning
confidence: 59%
“…It was suggested that use of acetate by facultative methanotrophs might be a survival strategy when the supply of methane is intermittent, and reports have shown that transcription of the pMMO genes continues under these conditions [39, 153–155]. In Methylocella silvestris , acetate repressed sMMO gene transcription, at least at the concentration tested (5 mM) [159, 160], although this was not the case for propane [44]. Recently, with the availability of additional genome sequences, Farhan Ul Haque et al [161] designed improved Methylocella -specific mmoX primers, which could be used to quantify Methylocella -like sMMO gene sequences in environmental samples.…”
Section: Environmental Occurrence and Ecologymentioning
confidence: 99%